THE IMPACT OF DISCIPLINE, MOTIVATION AND WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE AT BPJS KETENAGAKERJAAN REGIONAL OFFICE OF SOUTH SUMATRA AND BANGKA BELITUNG ISLANDS : A REVIEW - Sendri, Sendri; Helmi, Sulaiman; Trisninawati, Trisninawati; Roni, Mukran (LPPM STIE Muhammadiah Bandung, 2024)
This study aims to analyze the influence of work discipline, work motivation, and work environment on employee performance at the Social Security Administration Agency for Employment in the South Sumatra Regional Office. The SmartPLS method was used for analysis involving 110 respondents as the research sample. The research findings indicate that work discipline does not have a significant effect on employee performance (p = 0.838), while work motivation has been proven to significantly influence performance (p = 0.002). However, the work environment does not exhibit a significant impact on employee performance (p = 0.217). This study provides important insights into understanding the factors affecting employee performance in the Social Security Administration Agency, serving as a basis for companies to improve the work environment conditions and employee motivation. Moreover, it offers guidance for further studies concerning other variables that may affect employee performance in different work environments.